Influence of sex, age, and fasting on blood parameters and body, bursa, spleen and yolk sac weights of broiler chicks - Pires, D. L. [UNESP] (2007)
The effects of water and feed fasting for 24, 48 and 72 hours post-hatching on blood parameters (mean corpuscular volume, MCV; red blood-cell, RBC; hematocrit, HCT; hemoglobin, HGB; plasma glucose, CGP; plasma total protein, PP, and differential leukocytes count), and on body, liver, spleen, bursa, and yolk sac weights were analyzed. Erythrogram data were obtained with a blood cell counter. Total plasma protein and plasma glucose were determined by using the Bradford method (1976) and a glucose PAP liquiform kit (Labtest, cat. n. 84), respectively. Specific leukocyte counts were carried out on blood smears stained with Rosenfeld solution. According to the obtained data, water and feed post-hatching fasting reduced MCV values, which also were lower in males than that in females. Fasting for 48 hours promoted an increase in PP, while fasting for 72 hours reduced HCT. Chicks submitted to fasting presented lower body weights as compared to fed chicks, but their liver weight did not increase between 48 and 72 hours of age. Fasting decreased spleen weight, but bursa and yolk sac weight were not affected. Data showed that female and male chicks react in a similar way to post-hatching fasting, which affects body weight, liver and spleen weight, and HCT and PP values. Moreover, 72 hours of fasting affected more intensely HCT and MCV values.